Project Scheduling of Aruna Solar Power Plant Access Road and Pond Construction Using CPM and PERT - Aurellia Dianty; Lifia Citra Ramadhanti (Jurnal Serambi Engineering, 2026)
The success of construction projects is highly influenced by scheduling effectiveness, as project delays may lead to cost overruns, reduced productivity, and failure to achieve project targets. The Access Road and Pond Construction Project for the Aruna Solar Power Plant, undertaken by PT Wan Artha Nata Indonesia, experienced delays compared to the planned schedule. This study aimed to analyze project scheduling using the Critical Path Method (CPM) and Program Evaluation and Review Technique (PERT), identify critical activities, determine project completion duration, and evaluate schedule uncertainty. A descriptive quantitative approach with a case study design was employed. Data were collected through field observations, interviews, and project documentation, including the Work Breakdown Structure (WBS), project schedules, activity durations, and precedence relationships. CPM analysis was used to identify the critical path and determine the project duration, while PERT analysis was applied to evaluate schedule uncertainty using optimistic, most likely, and pessimistic time estimates. The results indicated that the minimum project duration was 203 days, with several activities identified as critical activities having no scheduling flexibility. Furthermore, the PERT analysis revealed the existence of schedule uncertainty caused by weather conditions, site constraints, material delivery delays, and permit approval processes.